Pelatihan Pembuatan Minuman Herbal Fungsional pada Ibu-Ibu PKK Desa Tiohu Kecamatan Asparaga Kabupaten Gorontalo - Netty Ino Ischak; Akram La Kilo; Weny J.A. Musa; Siti Romla Maspeke; Ambarwati Ambarwati (Universitas Negeri Gorontalo, 2022)
Tiohu is a village located in the Asparaga sub-district, Gorontalo Regency, in this village there are various types of herbal plants that are efficacious as traditional medicines. Temulawak, ginger, and turmeric are spices that are beneficial for health and can be made into instant powder ingredients that are brewed into functional drinks such as immune boosters and appetite enhancers. natural ones. This service program aims to hone the community's creativity in utilizing herbal plants to sell value products to help the family's economic source through the creative economy. This service is part of the KKNT-MBKM program, Department of Chemistry, State University of Gorontalo. The method used in this activity is to conduct training and practice herbal processing plants into instant drinks in the form of functional drink powders.